The Influence of Story Face Strategy and Reading Motivation toward the Tenth Grade Student’s Narrative Reading Comprehension Achievement of State Islamic Senior High School Number 1 of Palembang - Sri Murniati; Rusman Roni; Tahrun Tahrun (Universitas PGRI Palembang, 2018)
AbstractThis study was to investigate the influence of story face strategy and reading motivation towards reading comprehension achievement of the tenth grade students of State Islamic Senior High School Number 1 of Palembang. The population of this study was all the tenth grade students ofState Islamic Senior High School Number 1 of Palembang. The sample was 72 students were taken by using two-stage random sampling; cluster random sampling and simple random sampling technique. In carrying out the research, the writer used an experimental method; factorial design.The writer distributed pre-test, post-test, and reading motivation questionnaire in collecting thedata. Then, in analyzing the data, the writer used t-test and two-way ANOVA. The result of this study analysis that; First, there was a significant difference on reading comprehension achievement between the students who had high reading motivation and those who had low reading motivation taught by using story face strategy.Second, there was not any significant difference on reading comprehension achievement between the students who had high reading motivation and those who had low reading motivation taught by using conventional strategy. Third, there was a significantdifference on reading comprehension achievement between the students who had high reading motivation and those who had low reading motivation taught by using story face strategy and conventional teaching. The last, there was an interaction effect between story face strategy and students’ motivation on reading comprehension achievement of The Tenth Grade Students of State Islamic Senior High School Number 1 of Palembang.Keywords: Story face strategy, Motivation and Students’ Narrative Reading Comprehension Achievement.